Validation of the Urban Dispersion Model (UDM). (11th May 2004) - Brook, D.R.; Felton, N.V.; Clem, C.M.; Strickland, D.C.H.; Griffiths, I.H.; Kingdon, R.D.; Hall, D.J.; Hargrave, J.M.
The Urban Dispersion Model (UDM) was developed to satisfy a need of the UK Ministry of Defence to predict the dispersion of atmospheric pollutants within the urban environment. It is being subjected to an extensive validation and verification programme, which includes comparing model predictions against a comprehensive selection of measurements drawn from a database of field experimental trials. The model is compared here with three different field trials covering ranges from tens of metres to kilometres. The model predictions for maximum concentration along a given sampling line shows an average fractional bias of 0.22, a typical error of greater than 50% of the mean, and over 54% of the predictions are within a factor of 2 of the observations for the three data sets examined.